Glynn & Glynn, The Life And Death Of Smallpox - Salevouris, Michael (Teaching History: A Journal of Methods, 2005)
Edward Jenner, the discoverer of vaccination for smallpox, suggested in 1801 that the human race could now look forward to "the annihilation of the smallpox, the most dreadful scourge of the human species." In 1979 Jenner’s vision became a reality when a global commission confirmed that the worldwide eradication campaign, begun in the 1960s, had succeeded. This was surely one of the most notable human achievements in all of history. Yet, the world cannot rest easy. Stores of the deadly virus still reside in American and Russian laboratory freezers, and no one can be totally sure that there are no other secret repositories or that bioterrorists have not gotten their hands on the ultimate biological weapon.